2023
DOI: 10.3390/antiox12112010
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Properties and Geroprotective Potential of Wheat Bran Extracts with Increased Content of Anthocyanins

Daria V. Mikhailova,
Oksana G. Shevchenko,
Denis A. Golubev
et al.

Abstract: In recent years, there has been a focus on breeding wheat with high anthocyanin levels in order to improve food quality and human health. The objective of this study was to examine the antioxidant and geroprotective properties of wheat bran extracts using both in vitro and in vivo research methods. Two wheat lines were used: one with uncolored pericarp (anthocyanin-free) and another with colored pericarp (anthocyanin-containing). These lines differed in a specific region of chromosome 2A containing the Pp3/TaM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 96 publications
0
2
0
Order By: Relevance
“…The anthocyanin levels in both the whole-grain and bran extracts were higher in the colored line compared to the non-colored line [ 28 ]; the content of anthocyanins in the Gr_HCA was as high as 140 mM/g [ 26 ]. High-performance liquid chromatography with mass spectrometry of the wheat extracts revealed that the anthocyanin-enriched grain contains two major substances, cyanidin glucoside and cyanidin arabinoside, as well as several minor anthocyanins, while no anthocyanins were found in the bran extracts of the control grain [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The anthocyanin levels in both the whole-grain and bran extracts were higher in the colored line compared to the non-colored line [ 28 ]; the content of anthocyanins in the Gr_HCA was as high as 140 mM/g [ 26 ]. High-performance liquid chromatography with mass spectrometry of the wheat extracts revealed that the anthocyanin-enriched grain contains two major substances, cyanidin glucoside and cyanidin arabinoside, as well as several minor anthocyanins, while no anthocyanins were found in the bran extracts of the control grain [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the information on the health-promoting effects of wheat anthocyanins is very scant [ 15 ]. Recently, higher radical scavenging and membrane protective activities of wheat bran extract with a high level of anthocyanins have been found using mouse tissue homogenates (brain and testes) and suspension of murine erythrocytes [ 16 ]. Using mouse models of Parkinson’s and Alzheimer’s diseases, the neuroprotective activity of wheat anthocyanins has been demonstrated [ 17 ].…”
Section: Introductionmentioning
confidence: 99%